Efficacy of pethidine 0.1 and 0.2 mg/kg body weight as an adjuvant of intrathecal bupivacaine 0.5% 10 mg in preventing shivering - Djayanti Sari, Nur Hesti Kusumasari IG Ngurah Rai Artika (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Shivering related with spinal anesthesia commonly occurs in patients. It is not only uncomfortablefor the patients, but also related to some complication. The efficacy of pethidine in the preventionof shivering is well known. The aim of this study was to compare the efficacy of intrathecalpethidine 0.1 mg/kg body weight (BW) and 0.2 mg/kg BW as shivering-prevention drug afterspinal anesthesia. This was a randomized, double-blind controlled trial study involving 196subjects between the age 18-40 years with ASA physical status I-II, gestional age 37-42 weeks,BW of 40-70 kg or Body Mass Index (BMI) <30 kg/m2, body height >145 cm who underwent acaesarean delivery section with spinal anesthesia based of World Health Organization (WHO)procedure in cesarean delivery in Dr. Sardjito General Hospital, Yogyakarta and affiliated hospital.Subjects were divided into two groups with 98 subjects of each group. Group A was given anhyperbaric 0.5% bupivacaine 10 mg and pethidine 0.1 mg/kg BW, and Group B was given anhyperbaric 0.5% bupivacaine 10 mg and pethidine 0.2 mg/kg BW in the same volume (2.5 mL).The seubjects were observed for the incidence and severity of shivering and side effects ofpehtidine. The results showed that the incidence of shivering in Group A (35.70%) was significantlygreater than in Group B (22.44%) (p<0.05). However, the onzet an duration of shivering werenot significantly different in both groups (p>0.05). Moreover, the incidence of nausea andvomiting in Group A (8.33%) was significantly lower than Group B (22.45%). In conclusion,pethidine 0.2 mg/kg BW is more effective to preven shivering than pethidine 0.1 mg/kg BWalthough the incidence of its side effects is more higher.